Public Perspectives on The “Lapor Mas Wapres” Program on The Indonesian Lawyers Club YouTube Channel - Bella Putri Nur Habibah; Dyva Claretta (Publikasi Berkala Pendidikan Ilmu Sosial, 2025)
The transformation of information technology has created a new public space in digital media, which also serves as a political discourse arena. The "Lapor Mas Wapres" program, launched by Vice President Gibran Rakabuming Raka, is an interesting phenomenon that has received diverse responses from the public. This study aims to analyze the public's perspective on the program as presented through the Indonesia Lawyers Club (ILC) YouTube channel, specifically regarding the issue of political imagery. Using a qualitative descriptive method, this research explores the perceptions and interpretations of active ILC viewers who commented on the show "Lapor Mas Wapres // Between Appreciation and Imaging" in April-May 2025. Data was collected through observation of audience engagement on the platform and in-depth online interviews with purposefully selected active users. The analysis utilizes Stuart Hall's reception theory to identify dominant, negotiated, and oppositional readings. The results reveal a complex spectrum of public reactions, with the majority of informants in a negotiated position. They acknowledge the program's positive aspects but are skeptical about its consistency and real-world follow-up, often viewing it as a political gimmick rather than substantive public service.